Critical Notice: Thomas Sattig's The Double Lives of Objects: An Essay in the Metaphysics of the ordinary world, Oxford: Oxford University Press, 2015. Issue 1 (2nd January 2018) - Evnine, Simon J.
Abstract: This critical notice describes some of Thomas Sattig's book The Double Lives of Objects: An Essay in the Metaphysics of the Ordinary World and raises several critical issues about it.